2017
DOI: 10.1186/s12888-016-1173-2
|View full text |Cite|
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibitors versus placebo in patients with major depressive disorder. A systematic review with meta-analysis and Trial Sequential Analysis

Abstract: BackgroundThe evidence on selective serotonin reuptake inhibitors (SSRIs) for major depressive disorder is unclear.MethodsOur objective was to conduct a systematic review assessing the effects of SSRIs versus placebo, ‘active’ placebo, or no intervention in adult participants with major depressive disorder. We searched for eligible randomised clinical trials in The Cochrane Library’s CENTRAL, PubMed, EMBASE, PsycLIT, PsycINFO, Science Citation Index Expanded, clinical trial registers of Europe and USA, website… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
277
3
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(301 citation statements)
references
References 157 publications
(256 reference statements)
13
277
3
8
Order By: Relevance
“…In a recent systematic review, Jakobsen et al (2017) concluded that the potentially limited beneficial effects of antidepressants (SSRIs) appear to be outweighed by harmful effects. Critical voices have been raised against diagnostic practices and the potential adverse effects of psychiatric medication (Gøtzsche, 2013; Whitaker, 2010), and several authors have questioned the overreliance on biomedical models with regard to how we understand and manage suicidality (Cutcliffe & Santos, 2012; Hjelmeland, Dieserud, Dyregrov, Knizek, & Rasmussen, 2014; Marsh, 2016; Webb, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review, Jakobsen et al (2017) concluded that the potentially limited beneficial effects of antidepressants (SSRIs) appear to be outweighed by harmful effects. Critical voices have been raised against diagnostic practices and the potential adverse effects of psychiatric medication (Gøtzsche, 2013; Whitaker, 2010), and several authors have questioned the overreliance on biomedical models with regard to how we understand and manage suicidality (Cutcliffe & Santos, 2012; Hjelmeland, Dieserud, Dyregrov, Knizek, & Rasmussen, 2014; Marsh, 2016; Webb, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is my hope that Jakobsen et al (1) will see this comment on their work as an encouragement to reanalyse their data using the HDRS 6 total score as outcome measure. This would be a highly clinically relevant contribution to the literature.…”
mentioning
confidence: 90%
“…For the reasons outlined above, I strongly suggest that not only independent researchers like Jakobsen et al (1), but also organisations like the NICE, the pharmaceutical industry, and the pharmaceutical evaluation authorities, such as the US Food and Drug Administration and the European Medicines Agency, will no longer consider the total score on the HDRS (or the MADRS or BDI for that reason) as being a valid outcome measure in studies of antidepressants -because this practice is in conflict with the results of a very large body of literature based on clinical psychometric research. Furthermore, it is my hope that Jakobsen et al (1) will see this comment on their work as an encouragement to reanalyse their data using the HDRS 6 total score as outcome measure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vaaler sier at studien må ses i sammenheng med en metaanalyse publisert i fjor av 131 studier med over 27 000 pasienter om bruk av selektive serotoninreopptakshemmere (SSRI) (2). Forfatterne av den studien konkluderte med at SSRI-legemidler ikke hadde klinisk meningsfull effekt på depressive symptomer og at legemidlene økte risikoen for alvorlige og ikke-alvorlige bivirkninger.…”
unclassified